Consumer responses to covert advertising in social media - Göbel, F.; Meyer, A.; Ramaseshan, Balasubramani; Bartsch, S. (Emerald Group Publishing Limited, 2017)
© 2017, © Emerald Publishing Limited. Purpose: The purpose of this paper is to contribute to marketing communications literature by exploring consumer responses to covert advertising (CA) in a social media context. Design/methodology/approach: The persuasion knowledge model was used to explore the impact of CA on brand evaluations. A factorial design experiment was conducted in a social media context (YouTube). Findings: The results of the study show that triggering knowledge about CA changes the way consumers respond to unfamiliar brands that use such tactics. This implies that for unfamiliar brands, with future development of persuasion knowledge, CA in social media will not only be ineffective but also detrimental with damaging effects on the brand. Research limitations/implications: An important contribution of this study lies in the application of the persuasion knowledge model to social media context. Practical implications: The results indicate that firms should desist from covert product and brand communications in social media contexts, and instead employ disclosed brand communications. Originality/value: Given that the effects of CA have not been investigated in an online context, this study makes a unique contribution to brand communications research by providing valuable insights and better understanding of the effects of CA in social media, specifically YouTube.